Participatory Service Model for Strengthening Sustainable Poultry Farming in the Bontang Lestari Area, Bontang Regency, East Kalimantan - Dinar Anindyasari; Dede Aprylasari; Putri Daulika (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
This community service activity aims to empower small-scale poultry farmers in Bontang Lestari Village, Bontang City, East Kalimantan, through increasing technical, managerial, and institutional capacity. The implementation method includes identifying the potential problems of farmers, providing technical training based on local needs, and mentoring the formation of farmer cooperatives as a collective economic forum. A total of 30 farmers were actively involved in the entire series of activities. The activity results showed an increase in skills in making alternative feed, implementing biosecurity, and simple business records. Positive social impacts were also seen from the growth of community participation in group activities and joint marketing initiatives. This program shows that a participatory, potential-based, and collaborative approach can effectively strengthen the sustainability of community poultry farming businesses. This success is the basis for developing similar empowerment models in other areas with comparable characteristics.